Nuclear-encoded factors involved in post-transcriptional processing and modification of mitochondrial tRNAs in human disease - Powell, Christopher A.; Nicholls, Thomas J.; Minczuk, Michal (Frontiers in Genetics, 2015)
The human mitochondrial genome (mtDNA) encodes twenty-two tRNAs (mt-tRNAs) that are necessary for the intraorganellar translation of the thirteen mtDNA-encoded subunits of the mitochondrial respiratory chain complexes. Maturation of mt-tRNAs involves 5’ and 3’ nucleolytic excision from precursor RNAs, as well as extensive post-transcriptional modifications. Recent data suggest that over 7 % of all mt-tRNA residues in mammals undergo post-transcriptional modification, with over 30 different modified mt-tRNA positions so far described. These processing and modification steps are necessary for proper mt-tRNA function, and are performed by dedicated, nuclear-encoded enzymes. Recent growing evidence suggests that mutations in these nuclear genes, leading to incorrect maturation of mt-tRNAs, are a cause of human mitochondrial disease. Furthermore, mtDNA mutations in mt-tRNA genes, which may also affect mt-tRNA function, processing and modification, are also frequently associated with human disease. In theory, all pathogenic mt-tRNA variants should be expected to affect only a single process, which is mitochondrial translation, albeit to various extents. However, the clinical manifestations of mitochondrial disorders linked to mutations in mt-tRNAs are extremely heterogeneous, ranging from defects of a single tissue to complex multisystem disorders. This review focuses on the current knowledge of nuclear genes coding for proteins involved in mt-tRNA maturation that have been linked to human mitochondrial pathologies. We further discuss the possibility that tissue specific regulation of mt-tRNA modifying enzymes could play an important role in the clinical heterogeneity observed for mitochondrial diseases caused by mutations in mt-tRNA genes.